1996
DOI: 10.1073/pnas.93.12.5883
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent oligonucleotide antagonists specific for L-selectin.

Abstract: The selectins are calcium-dependent C-type lectins that recognize complex anionic carbohydrate ligands, initiating many cell-cell interactions in the vascular system. Selectin MATERIALS AND METHODSMaterials. The sources of most of the materials used are noted in the individual methods sections or in the figure legends. All other chemicals used were of reagent grade and/or the highest quality available.SELEX for Isolation of L-Selectin Ligands. L-selectin receptor globulin (LS-Rg) was prepared as described (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 37 publications
0
74
0
Order By: Relevance
“…In order to increase the specificity of selected RNA aptamers, we have utilized a combinatorial library approach by pretreating RNA aptamers with GST-Sepharose 4B before each round of SELEX selection, from the third round to the eighth and final round. Although this combinatorial library approach has been successfully used to isolate aptamers blocking ligand-receptor interactions between eukaryotic cells and viruses (2,5,8) or between eukaryotic cells themselves (17,22,29), the technique has not been applied to the selection of ligands blocking an interaction between bacterial and eukaryotic cells. Our studies indicate that the SELEX approach is a useful tool to study the roles of bacterial proteins in pathogenesis and invasion of host cells, as well as to provide insights into the mechanisms of pathogen-host cell interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the specificity of selected RNA aptamers, we have utilized a combinatorial library approach by pretreating RNA aptamers with GST-Sepharose 4B before each round of SELEX selection, from the third round to the eighth and final round. Although this combinatorial library approach has been successfully used to isolate aptamers blocking ligand-receptor interactions between eukaryotic cells and viruses (2,5,8) or between eukaryotic cells themselves (17,22,29), the technique has not been applied to the selection of ligands blocking an interaction between bacterial and eukaryotic cells. Our studies indicate that the SELEX approach is a useful tool to study the roles of bacterial proteins in pathogenesis and invasion of host cells, as well as to provide insights into the mechanisms of pathogen-host cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial self-association is an important virulence trait in enterotoxigenic strains of Escherichia coli and in Vibrio cholerae (1). These data indicated that the structural protein PilS of the type IVB pili might play important roles in the pathogenesis of S. enterica serovar Typhi in humans.The SELEX (systematic evolution of ligands by exponential enrichment) method (28) is an oligonucleotide-based combinatorial library selection procedure that has been used extensively to isolate ligands (aptamers) that bind to proteins (3,6,9,22,32), cell surface epitopes (19,21), and other targets (4,12,13,17). Although in recent years SELEX has become increasingly important in the study of functions of proteins, as well as in the fields of drug discovery and identification of antagonists against many functional proteins, this in vitro selection strategy to generate inhibitors of the functions of bacterial proteins remains underutilized.…”
mentioning
confidence: 99%
“…that published for E-selectin (Scheffler et al, 1995), will be conducive for this approach. Reduction of cross-reactions between selectins can be sought to be attained by systematic evolution of ligands with the exponential enrichment technology, as shown for isolation of oligonucleotide ligands for L-selectin surpassing the binding affinity of common oligosaccharides by a factor of IO4-1O5 (O'Connell et al, 1996). RNA molecules can thus apparently form surfaces that mimic those of oligosaccharides and also those of proteins, as has already been documented (Keene, 1996).…”
Section: C-type Lectinsmentioning
confidence: 99%
“…The aptamers were tested for selectivity using only protein targets: full-length BACE1 coupled to agarose and an antibody-derivatized agarose. Other selections of RNA aptamers against soluble extracellular fragments of membrane proteins, albeit without any testing for selectivity, were reported for: L-selectin (a cell adhesion molecule) [24], β-catenin (a component of the Wnt signaling pathway) [25] and KRAS protein (a molecular switch in the propagation of receptor signals related to cell proliferation, division and mortality) [26]. There were two reports on selections of DNA aptamers against soluble extracellular fragments of the following membrane proteins: hemagglutinin (located in the influenza virus envelope) [27] and MUC1 (located in the membrane of epithelial cells and overexpressed on some cancer cells) [28].…”
Section: Aptamers Selected Using Soluble Fragments Of Membrane Proteinsmentioning
confidence: 99%